2008
DOI: 10.1182/blood.v112.11.263.263
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Significant Responses Achieved with Romidepsin in Treatment-Refractory Cutaneous T-Cell Lymphoma: Final Results from a Phase 2B, International, Multicenter, Registration Study

Abstract: Background: Responses to romidepsin, a novel pan-HDAC inhibitor, have been observed in patients (pts) with cutaneous T-cell Lymphoma (CTCL). This Phase 2B, singlearm, open-label registration study enrolled pts with CTCL (Stages IB–IVA) at 33 European and US sites. Pts with histologically confirmed CTCL who failed ≥1 prior systemic therapy, had adequate organ function, and ECOG PS 0 or 1 were eligible. Exclusions included significant cardiovascular abnormality or treatment with QTc-prolonging or CYP3A4-inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…But some of the effects of HDAC inhibitors may also hamper therapeutic efficacy. Examples are the increased expression of multi-drug resistance proteins that lead to increased cellular efflux of chemotherapeutic agents (Tabe et al 2006 ; Kim et al 2008a , b ).…”
Section: Effects Of Hdac Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…But some of the effects of HDAC inhibitors may also hamper therapeutic efficacy. Examples are the increased expression of multi-drug resistance proteins that lead to increased cellular efflux of chemotherapeutic agents (Tabe et al 2006 ; Kim et al 2008a , b ).…”
Section: Effects Of Hdac Inhibitionmentioning
confidence: 99%
“…The cyclic peptide Romidepsin is the second HDACi approved by the FDA in November 2009 for the treatment of CTCL of patients who had received at least one prior systemic therapy. The approval was based on two single-arm, multicenter, open-label trials in which 167 patients were treated (Kim et al 2008a , b ; Piekarz et al 2009a , 2009b ). Romidepsin can be administered at 14 mg/m 2 intravenously over 4 h on days 1, 8, and 15 of a 28-day cycle.…”
Section: Clinical Trials Of Romidepsinmentioning
confidence: 99%
“…Currently, these drugs have their principal application in the treatment of MDS and cutaneous T‐cell lymphoma (CTCL), but are being evaluated in a variety of other settings (128). In the phase 2B, registration study of romidepsin in treatment‐refractory CTCL, TLS was reported in 2% of patients (129). Two patients with MM developed grade 4 TLS in a phase I dose‐escalating study of the investigational HDACI belinostat in 16 patients with advanced hematologic neoplasms.…”
Section: Tumour Lysis Syndrome With Targeted Therapiesmentioning
confidence: 99%
“…In vitro it has shown a strong activity against HDAC 1 and 2, but also against HDAC 6 and HDAC 4, although it results to be weaker (Mai and Altucci 2009 ). The drug has been in clinical trials for CML and AML (Byrd et al 2005 ; Piekarz et al 2004 ) and has been approved in November 2009 for the treatment of refractory–relapsed CTCL (Kim et al 2008 ).…”
Section: Hydroxamic Acidsmentioning
confidence: 99%